ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) PDAM KOTA MAKASSAR - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2011)
Management of human resources could be argued that dealing with the form and character of the personnel functions of the organization where the main activity is to get human resources. Human management of human resources by using the four steps that is the problem, evaluation of practice runs, human resources management system and system implementation planning, preparation and development of employees.